Pharmacology, Pharmacotherapy, and Pharmacopolicy Through an Evidence-Based Medicine: A Novel Approach for First-Year Medical Students - Alexander M. Mozeika; Rijul Asri; James F. Theis; Carolyn K. Suzuki (Association of American Medical Colleges, 2020)
Introduction As evidenced by student performance on various assessments, pharmacotherapy remains a comparative weakness in undergraduate medical education, with several institutions developing novel strategies for students to apply these principles in a practical setting. Medical curricula have recently prioritized group-learning modalities and evidence-based medicine education. However, these principles have yet to impact pharmacology education. We developed and implemented an evidence-based, group-learning exercise for first-year medical students focusing on pharmacology through the practical lens of pharmacotherapy and pharmacopolicy. Methods First-year medical students in different groups were assigned a particular medication and, during an in-class session, were encouraged to meet with other representatives assigned the same drug to interpret the provided package insert and any online information. Students then reconvened with their groups to engage in collaborative teaching about each assigned drug before completing a group quiz using online resources. Facilitators reviewed the group quiz and allowed time for student questions. Results For 180 participants, the average group-quiz score was 86%, ranging from 68% to 100%. Student-reported satisfaction with the activity in meeting its preset objectives averaged 3.7 on a 5-point scale, with 5 being most positive. Discussion Overall, this activity effectively integrates principles of pharmacotherapy and pharmacopolicy into a group-based, evidence-based exercise. Limitations of the activity include the number of possible example drugs and the amount of material covered in a given time frame. However, the activity lends itself to the role of an introductory session in a longer curriculum centered on clinical-applied pharmacology and evidence-based practice.